HUBUNGAN MINUMAN ISOTONIK DENGAN KONSUMSI OKSIGEN MAKSIMAL PADA MAHASISWA JPOK UNLAM BANJARBARU - Azizah, Azizah; Biworo, Agung; Asnawati, Asnawati (Jurnal Berkala Kedokteran, 2015)
Maximum oxygen consumption (VO2 max) is the maximum number of individual oxygen that can be used during the exercise and is one of the good measurements of cardiorespiratory fitness. Isotonic drink is one of the drinks that supplies the energy and fluid balance during the exercise.  This research aims to determine whether there is a relationship of isotonic drink with maximum oxygen consumption. This research uses quasi experimental  pretest and posttest design.  The population of this research are the students of JPOK UNLAM Banjarbaru, who were divided into two groups based on before and after giving isotonic drinks. The method of retrieval research subjects is by purposive sampling method, with 33 respondents of the research subjects. The measurement of VO2 max is conducted by using multistage fitness test. The average value of VO2 max before giving isotonic drinks was 45,05 ml/kg/minute and after giving it became 49,34 ml/kg/minute. The paired t test with confidence level 95% showed significant differences in both of the data with the value of p = 0,000, it can be concluded that isotonic drinks can increase VO2 max. Keywords:  isotonic, VO2 max.